Factorial Classification of Consumers for Bamboo-based Products in Haiti: Importance and Perceived Benefits - Francois, Daphney; Liaw, Shu-Yi; Nguyen, Giang Thi (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2021)
Recently, the use of bamboo as a material in construction and else is very typical almost everywhere in the world. Bamboo stems are able to produce after processing a variety of products ranging from household items to industrial and other applications. The purpose of this study is to identify and classify the homogenous cases that have similar needs and knowledge about the importance application and benefits of bamboo. The questionnaires were completed by 378 respondents in Haiti. The results from K-mean clustering analysis show the three groups identified were namely Functional, Aggressive, and Potential groups. The Functional group was high knowledge about important application factors and low knowledge about benefit factors. While Aggressive group was high in both factors. Besides, the Potential group with the lowest one needing improvement on both factors. This study may suggest to the Haitian population to facilitate investment and promotion of bamboo products in both national and international markets in the country.